What's In a Name? : That Which We Call Capital Controls - Ghosh, Atish (IMF Working Papers; Working Paper, 2016)
This paper investigates why controls on capital inflows have a bad name, and evoke such visceral opposition, by tracing how capital controls have been used and perceived, since the late nineteenth century. While advanced countries often employed capital controls to tame speculative inflows during the last century, we conjecture that several factors undermined their subsequent use as prudential tools. First, it appears that inflow controls became inextricably linked with outflow controls. The latter have typically been more pervasive, more stringent, and more linked to autocratic regimes, failed macroeconomic policies, and financial crisis-inflow controls are thus damned by this "guilt by association." Second, capital account restrictions often tend to be associated with current account restrictions. As countries aspired to achieve greater trade integration, capital controls came to be viewed as incompatible with free trade. Third, as policy activism of the 1970s gave way to the free market ideology of the 1980s and 1990s, the use of capital controls, even on inflows and for prudential purposes, fell into disrepute.